Optimized synthesis and electrochemical behaviors of Prussian blue analogues cathodes for potassium-ion batteries - Long Cheng; Yuanyi Luo; Hao Wang; Zhiyue Zhou; Mengkai Yang; Chen Li; Yujie Zheng; Meng Li; Lei Wang; Kuan Sun (Materials Reports: Energy)
The superior adaptability of Prussian blue analogues (PBAs) in interacting with potassium ions has shifted research focus toward their potential application as cathodes of potassium-ion batteries (PIBs). The large interstitial space formed between metal ions and –C≡N– in PBAs can accommodate large-radius K+. However, the rapid nucleation in the co-precipitation synthesis process of PBAs induces many lattice defects of [M(CN)6]4− vacancies (V[M–C≡N]), interstitial and coordinated H2O molecules, which will directly lead to performance degradation. Moreover, originating from various transition metal elements in low/high-spin electron configuration states, PBAs exhibit diverse electrochemical behaviors, such as low reaction kinetics of low-spin iron (II), Jahn-Teller distortion and dissolution of manganese (III), and electrochemical inertness of nickel (II) and copper (II). Here, we summarize recently reported structures and properties of PBAs, classifying them based on the types of transition metals (iron, cobalt, manganese, copper, nickel) employed. Advanced synthesis strategies, including control engineering of crystallinity based on H2O molecules and V[M–C≡N], were discussed. Also, the approaches for enhancing the electrochemical performance of PBAs were highlighted. Finally, the challenges and prospects towards the future development of PBAs are put forward. The review is expected to provide technical and theoretical support for the design of high-performance PBAs.